In vitro antiviral activity of plant extracts from Asteraceae medicinal plants - Visintini Jaime, María Florencia (2013)
Due to the high prevalence of viral infections having no specific treatment and the constant appearance of resistant viral strains, the development of novel antiviral agents is essential. The aim of this study was to evaluate the antiviral activity against bovine viral diarrhea virus, herpes simplex virus type 1 (HSV-1), poliovirus type 2 (PV-2) and vesicular stomatitis virus of organic (OE) and aqueous extracts (AE) from: Baccharis gaudichaudiana, B. spicata, Bidens subalternans, Pluchea sagittalis, Tagetes minuta and Tessaria absinthioides. A characterization of the antiviral activity of B. gaudichaudiana OE and AE and the bioassay-guided fractionation of the former and isolation of one active compound is also reported. Methods: The antiviral activity of the OE and AE of the selected plants was evaluated by reduction of the viral cytopathic effect. Active extracts were then assessed by plaque reduction assays. The antiviral activity of the most active extracts was characterized by evaluating their effect on the pretreatment, the virucidal activity and the effect on the adsorption or post-adsorption period of the viral cycle. The bioassay-guided fractionation of B. gaudichaudiana OE was carried out by column chromatography followed by semipreparative high performance liquid chromatography fractionation of the most active fraction and isolation of an active compound. The antiviral activity of this compound was also evaluated by plaque assay. Results: B. gaudichaudiana and B. spicata OE were active against PV-2 and VSV. T. absinthioides OE was only active against PV-2. The corresponding three AE were active against HSV-1. B. gaudichaudiana extracts (OE and AE) were the most selective ones with selectivity index (SI) values of 10.9 (PV-2) and >117 (HSV-1). For this reason, both extracts of B. gaudichaudiana were selected to characterize their antiviral effects. Further bioassay-guided fractionation of B. gaudichaudiana OE led to an active fraction, FC (EC50=3.1 μg/ml; SI= 37.9), which showed antiviral activity during the first 4 h of the viral replication cycle of PV-2 and from which the flavonoid apigenin (EC50 = 12.2 ± 3.3 μM) was isolated as a major compound. Conclusions: The results showed that, among the species studied, B. gaudichaudiana seemed to be the most promising species as a source of antiviral agents.